Julia Kristeva and the Psychological Dynamics of Writing - Janet M. Ellerby (Journal of the Assembly for Expanded Perspectives on Learning, 1997)
By tapping into latent emotional dynamics, Kristeva's poststructuralist psychology offers a means to modify the cognitive order emphasized in academic discourse.